Student Self-Responsibility in the Indonesian Distance Education System - Daudi Lazarus (Forum Dosen Indonesia, 2017)
An ongoing concern in the distance education system in Indonesia is students’ lack of commitment to ‘independent study’. The purpose of this paper is to review conceptual frameworks that could empower Indonesian students to accept responsibility for their learning at a level to address the learning challenges of distance education. The review shows that to meet quality and equity expectations in online distance education, independent study modes should promote students’ self-responsibility based primarily on both autonomy and capability. The findings have the potential to add new perspective to education through supporting teaching and learning approaches in an online distance education class to enhance self-responsibility. The paper suggests that students would take more control of independent learning if they accepted primary responsibility to determine their learning needs, resources, activities and outcomes. To do this they need to view themselves as active agents with power to take independent choices that can result in creating their own approaches to resolve their learning limitation.